E/E′ Is a New Independent Predictor of Recovered Ejection Fraction in Patients With Systolic Heart Failure Undergoing Ablation for Atrial Fibrillation - Yang, Minghui; Zhang, Rongfeng; Tang, Huamin; Li, Guocao; Guan, Xumin; Yang, Yiheng; Sun, Yuanjun; Xiao, Xianjie; Yu, Xiaohong; Yin, Xiaomeng; Dong, Yingxue; Gao, Lianjun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Catheter ablation should be considered in selected atrial fibrillation patients with HFrEF to improve survival and reduce HF hospitalization. Careful patient selection for AF ablation is key important to achieve similar outcome benefits. However, limited data exist regarding predictors of recovered ejection fraction. Our aim was evaluation of the predictors of recovered EF in consecutive heart failure patients undergoing ablation for atrial fibrillation. Methods and results A total of 156 patients [67.3% male, median age 63 (11)] with AF and HF underwent an initial catheter ablation between September 2017 and October 2019 in First Affiliated hospital of Dalian Medical University. Overall, the percentage of recovered ejection fraction was 72.3%. Recovered EF was associated with a 39% reduction in all cause hospitalization compared to non-recovered EF for 1 year follow up (23.8 vs. 62.8, OR 2.09[1.40-3.12]). Univariate analysis for recovered EF showed that diabetes (P = 0.083), Prevalent HF (P = 0.014), Prevalent AF(P = 0.051), LVEF(P = 0.022), and E/E’(P = 0.001) is associated with EF improvement. Multivariate analysis showed that the only independent predictor of EF recovered was [odds ratio (OR) 1.13; 95% CI 1.03–1.24; P = 0.011]. A receiver operating characteristics analysis determined the suitable cut-off value for E/E’ was 15(sensitivity 38.7%, specificity 89.2%, area under curve 0.704) Conclusion EF recovered occurred in 72.3% patients which was associated with a 39% reduction in all cause hospitalization compared to non-recovered EF ejection fraction in our cohort. The only independent predictor of recovered EF was E/E’<15 in our series.